Plunge cylindrical grinding with the minimum quantity lubrication coolant technique assisted with wheel cleaning system - Bianchi, Eduardo Carlos [UNESP]; Rodriguez, Rafael Lemes [UNESP]; Hildebrandt, Rodolfo Alexandre [UNESP]; Lopes, Jose Claudio [UNESP]; Mello, Hamilton Jose de [UNESP]; Silva, Rosemar Batista da; Aguiar, Paulo Roberto de [UNESP] (Springer, 2018)
MQL technique is considered as a cleaner machining compared to the conventional coolant delivery one, thereby ensuring environmental sustainability and economic benefits. However, one of problems commonly reported when using the MQL technique is the wheel clogging phenomenon as a result of the inefficient chip removal from the cutting zone, then the chips lodge inside the pores of the grinding wheel, adversely affecting the quality and the finishing of the final product. In this context, this study was carried out to evaluate the performance of the minimum quantity lubrication coolant technique assisted with a wheel cleaning jet (MQL + WCJ) in plunge grinding of hardened steel. This cooling-lubrication technique was tested using the following flow rates: 30, 60, and 120 ml/h. Comparative tests were also carried out with the conventional coolant technique, as well as with the traditional MQL technique (without the wheel cleaning jet). The output variables used to assess the efficiency of the MQL + WCJ technique are roughness, roundness, workpiece microhardness, grinding wheel wear, and power consumption. The results showed that the machining with the MQL + WCJ technique outperformed the traditional MQL technique in all the output parameters investigated. Also, the efficiency of the MQL + WCJ technique increased with flow rate, thereby being an alternative coolant delivery technique in grinding due to cleaner environment, more sustainable and lower consumption of fluid compared to conventional coolant one. No thermal damages and cracks on the machined surface and sub-surfaces were observed after grinding AISI 4340 steel, irrespective of the technique.
Keywords: Cylindrical grinding; MQL technique; Wheel cleaning; Roughness; Surface integrity